Potential impact of bauxite mining activity on water quality at Sungai Penggorak, Kuantan catchment area - Azza Nurshafira, Zul' Azman (2017)
Bauxite mining has become a serious matter to ponder in Malaysia. In 2013, a total of 236 mine sites are identified to produce and transport bauxite but only 36 are legal.This irresponsible act gives serious impact to the local Kuantan community such as air pollution, water pollution, ecosystem degradation and bring discomfort to people. Sungai Pengorak (Pengorak river), Kuantan is one of the affected area due to bauxite mining. The purpose of this study is to evaluate the spatial variation of bauxite affected river water quality in Sungai Pengorak Kuantan, to classify the river water by assessing the water quality according to the Normal Water Quality Standard (NWQS) and to make recommendations and suggestions for sustainable bauxite management of the river system. In-situ parameters and ex–situ tests were conducted to obtained the results. The river water sample was taken from three (3) different point source, as much as three (3) times to conduct the water quality analysis. HORIBA meter was used to record the in – situ parameters data. Ten (10) paramenters were chosen to be analysed which were pH, turbidity, temperature, electrical conductivity (E.C), dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), hardness and heavy metals. The results of parameters obtained were classified according to NWQS. pH value recorded as high as 7.42 at Station 1 and as low as 6.14 at Station 3 and it is within NWQS standard. Next, the highest temperature recorded among the stations was 27.9 °C while the lowest was 27.6 °C. The turbidity recorded exceeded the 5mg/l standard range with 57 mg/l at Station 1 while the lowest was 43 mg/l at Station 3. As for total suspended solids, the highest value obtained was 48 mg/l at Station 3 and 16 mg/l at Station 1 and the standard range was 25 mg/l. High concentration of turbidity and total suspended solids was due to the discharge of unregulated mine waste from nearby mine site. Hardness was the highest at Station 1 with 5.69 mg/l while the lowest with 1.51 mg/l at Station 2. Sungai Pengorak is considered soft water because the values recorded does not exceeded the NWQS standard which is 250 mg/l. As for dissolved oxygen concentrations, the highest was 4.17 mg/l at Station 3 while the lowest was 3.75 mg/l at Station 1. The highest biochemical oxygen demand value (8.86 mg/l) was recorded at Station 1 while the lowest value (6.53 mg/l) recorded at Station 2. The highest chemical oxygen demand value (47 mg/l) was recorded at Station 3 while the lowest value (30 mg/l) recorded at Station 2. The values of all concentrations were highly exceeded the NWQS standard. It is due to the bauxite mining activity conducted at nearby area. In addition, the electrical conductivity was recorded the highest of 1200 μS/cm at Station 3 while the lowest of 854 μS/cm at Station2. High electrical conductivity indicates high ions concentrations in the water and vice versa. Analysed heavy metals concentration towards the water found that chromium was the highest in concentration which is 0.45 mg/l, followed by iron 0.3 mg/l, copper 0.05 mg/l and cadmium 0.09 mg/l. All of the heavy metals exceeded the NWQS standard of 0.05 mg/l each. In a nutshell, the river is classified overall to its water classes as Class IV at Station 1 and Station 3 while Class III at Station 2. For future use of water, precautions measures should be implemented. Water quality laws should be reinforced, environmental education should be implemented and „polluters pay principle‟ should be practiced so that the community is aware of the problem and the problem can be reduced even if it takes time.